Stretchable Redox‐Active Semiconducting Polymers for High‐Performance Organic Electrochemical Transistors. Issue 23 (2nd May 2022) - Dai, Yahao; Dai, Shilei; Li, Nan; Li, Yang; Moser, Maximilian; Strzalka, Joseph; Prominski, Aleksander; Liu, Youdi; Zhang, Qingteng; Li, Songsong; Hu, Huawei; Liu, Wei; et al.
Abstract: Organic electrochemical transistors (OECTs) represent an emerging device platform for next‐generation bioelectronics owing to the uniquely high amplification and sensitivity to biological signals. For achieving seamless tissue–electronics interfaces for accurate signal acquisition, skin‐like softness and stretchability are essential requirements, but they have not yet been imparted onto high‐performance OECTs, largely due to the lack of stretchable redox‐active semiconducting polymers. Here, a stretchable semiconductor is reported for OECT devices, namely poly(2‐(3, 3′‐bis(2‐(2‐(2‐methoxyethoxy)ethoxy)ethoxy)‐[2, 2′‐bithiophen]‐5)yl thiophene) (p(g2T‐T)), which gives exceptional stretchability over 200% strain and 5000 repeated stretching cycles, together with OECT performance on par with the state‐of‐the‐art. Validated by systematic characterizations and comparisons of different polymers, the key design features of this polymer that enable the combination of high stretchability and high OECT performance are a nonlinear backbone architecture, a moderate side‐chain density, and a sufficiently high molecular weight. Using this highly stretchable polymer semiconductor, an intrinsically stretchable OECT is fabricated with high normalized transconductance (≈223 S cm −1 ) and biaxial stretchability up to 100% strain. Furthermore, on‐skin electrocardiogram (ECG) recording is demonstrated, which combines built‐in amplification and unprecedented skin conformability. Abstract : A high‐performance redox‐active semiconducting polymer with stretchability up to 200% strain and 5000 repeated cycles is reported. The strain‐induced electrical performance and structural evolution are systematically studied. An intrinsically stretchable organic electrochemical transistor (OECT) is fabricated to give the a normalized G m of 233 S cm −1 and biaxial stretchability up to 100% strain. Real‐time on‐skin electrocardiogram signal recording is realized.